THE ROLE OF REGIONAL “ADVANCED VOCATIONAL MASTERY TECHNICUMS” IN IMPROVING THE QUALIFICATIONS OF PEDAGOGICAL CADRES BASED ON THE CLUSTER MODEL (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the activities of the new institutional structure – “Advanced Vocational Mastery Technicums” (Advanced Professional Skill Colleges), introduced in the vocational education system in accordance with the Resolution of the President of the Republic of Uzbekistan No. PQ-316 dated October 23, 2025. It scientifically substantiates the function of these technicums, established in the regions, as an educational cluster center (Hub) serving as a leading practical base for other technicums in the region. Furthermore, the article elucidates new mechanisms that ensure the integration of resource efficiency and educational quality in improving the qualifications of production training masters.